2022
DOI: 10.2147/hiv.s372204
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Falls in HIV-Infected Patients on Antiretroviral Therapy and Its Associated Factors

Abstract: Purpose Fall is one of the geriatric syndromes and a significant public health concern, which causes potentially severe consequences among the elderly. Geriatric syndromes are common among PLHIV and affect younger age than the general population. This study attempted to identify the risk of falls in PLHIV on antiretroviral therapy (ART) and its related factors among older adults with HIV infection. Methods This cross-sectional study was conducted from December 2019 to M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It should also be noted that the start of our study period was 2012, and newer antiretroviral regimens approved since the start of the study period in general may have improved safety profiles, including in older PWH. Second, the study design did not allow for the quantitative capture of measures such as frailty, neuropathy, or other physical factors that are associated with fall risk, as previous studies have identified frailty as well as imbalance symptoms as being associated with an increased risk of falls in PWH [ 22 , 30 ]. The study was conducted at only one site, and although the demographics are similar to many inter-city HIV clinics, this limits the generalizability of the results.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that the start of our study period was 2012, and newer antiretroviral regimens approved since the start of the study period in general may have improved safety profiles, including in older PWH. Second, the study design did not allow for the quantitative capture of measures such as frailty, neuropathy, or other physical factors that are associated with fall risk, as previous studies have identified frailty as well as imbalance symptoms as being associated with an increased risk of falls in PWH [ 22 , 30 ]. The study was conducted at only one site, and although the demographics are similar to many inter-city HIV clinics, this limits the generalizability of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies reported an increased risk for falls among PWH compared with the general population, with PWH experiencing falls at a younger age compared with adults without HIV [ 38 ]. Our results indicate that polypharmacy and hyperpolypharmacy, in particular, are strongly associated with a higher risk for recurrent falls among PWH.…”
Section: Discussionmentioning
confidence: 99%